Desain Lanskap Riparian Sungai Tole dengan Konsep Eco-Culture di Kota Bungku, Kecamatan Bungku Tengah, Kabupaten Morowali - Ikram; Rani, Medria Shekar (Jurnal Lanskap Indonesia, 2025)
The alteration of land use along the riverine corridor has resulted in a reduction in the water catchment area that increases the frequency and severity of flooding events. In addition, the erosion of soil material during periods of high rainfall has contributed to the accumulation of sediment within the riverine, further exacerbating the issue of waterlogging. The location of urban recreation facilities in Bungku City, situated in coastal and mountainous areas, has prompted the local community to consider the Tole River as a potential new urban recreation area. The objective of this design is to create a riverine riparian landscape that mitigates sedimentation and flooding. This is pursued through the implementation of soil bio-engineering techniques, including the use of vegetated rock gabion walls, contour wattling, vegetation, and mangrove plants to minimise erosion. The resolution of cultural issues entails the revitalization of community activities in the vicinity of the river. This is pursued by the provision of facilities, including a food court area, a dance plaza, a fishing area, a green amphitheater, a playground area, a reading room, a gazebo, a canoe tour, a fishing boat parking area, and a viewing deck. The implementation of the eco-culture concept within the riparian landscape design of the Tole River incorporates facilities such as greenhouses, botanical gardens, retention ponds, and wetland areas, which are interconnected by pedestrian and bicycle pathways, as well as eco-ways. It is anticipated it will foster a harmonious balance between the ecological and the cultural aspects of the Bungku City community.